Analysis of The Commercial Court’s Decision on The Postponement of Debt Payment Obligations to Life Insurance Companies Without The Approval of The Financial Service Authority: Case Study Case Number 389/Pdt.Sus-PKPU/2020/PN Niaga Jkt. Pst - Amalia, Siti; Judge, Zulfikar (Jurnal Legisci, 2023)
The Financial Services Authority (hereinafter referred to as "OJK") is an institution that has the authority to attribution has been established and appointed by the government to carry out regulatory and supervisory functions for Financial Service Institutions, one of which is in the case of requests for Suspension of Debt Payment Obligations (hereinafter referred to as "PKPU") at life insurance companies. This research was motivated by the issuance of a PKPU ruling against PT. Kresna Life Insurance (hereinafter referred to as "PT. AJK) by the Commercial Court based on the application of Lukman Wibowo as one of PT AJK's customers and creditors. The problem that arises is that OJK as an institution that has the authority does not respond to the application submitted by the customer in question within the period prescribed by law. This study examines and analyzes the Commercial Court Decision against PKPU at PT. AJK (Case Study Number 389/Pdt.Sus PKPU/2020/PN Niaga Jkt.Pst). The research method used in this study is normative or doctrinal legal research. The results of the study found that the PKPU was not in accordance with applicable laws in Indonesia, because legally the authority to apply for PKPU is absolutely in the hands of the OJK.